FAKTOR-FAKTOR YANG MEMPENGARUHI PARTISIPASI IBU DALAM PENIMBANGAN BALITA DI WILAYAH KERJA PUSKESMAS PARDAMEAN KOTA PEMATANGSIANTAR - Agnes Sry Vera Nababan; Melva Rinawati Butar-Butar; Yulita .; Rani Suraya (Fakultas Kesehatan Masyarakat Institut Kesehatan Medistra Lubuk Pakam, 2021)
Abstract One indicator of community participation in the health sector is the coverage of children under five who come and are weighed at the posyandu (D / S). Based on the 2018 Indonesian Health Profile, D / S coverage for toddlers in Indonesia is 67.48%. Some of the factors causing the lack of maternal visits to the posyandu were the mothers' lack of knowledge, the distance to the Posyandu, the role of cadres and family support. Of this study was to determine the factors that influence the participation of mothers in weighing children under five in the working area of ??Pardamean Health Center, Pematangsiantar City. This research method is an analytic study with cross-sectional design with 108 respondents by purposive sampling. The subject is the mother of the toddler who meets the inclusion and exclusion criteria. Primary data were collected in the Pardamean Puskesmas area on 12th - 10th . Based on the statistical test of 108 mothers of children under five, there were still 41 mothers who did not participate in weighing children under five by 38%. The results of the chi square analysis show that the relationship between maternal knowledge and maternal participation in weighing children under five is obtained by the p value = 0.000 (p <0.05), the relationship between Posyandu distance and maternal participation in weighing children under five is obtained by the p value = 0.002 (p <0.05) , the correlation between the role of cadres and the participation of mothers in weighing children under five, is obtained by the p value = 0.000 (p <0.05), the relationship between family support and the participation of mothers in weighing children under five is obtained by the p value = 0.017 (p <0.05). That there is a relationship between maternal knowledge, Posyandu distance, the role of cadres and family support in weighing toddlers in the working area of ??Pardamean Health Center, Pematangsiantar City. Keywords : Mother's Knowledge, Posyandu Distance, Role of Cadres, Family Support, Mother's Participation.